2010
DOI: 10.1007/s12665-010-0605-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization on soil respiration in temperate grassland in Inner Mongolia, China

Abstract: Nitrogen addition to soil can play a vital role in influencing the losses of soil carbon by respiration in N-deficient terrestrial ecosystems. The aim of this study was to clarify the effects of different levels of nitrogen fertilization (HN, 200 kg N ha -1 year -1 ; MN, 100 kg N ha -1 year -1 ; LN, 50 kg N ha -1 year -1 ) on soil respiration compared with non-fertilization (CK, 0 kg N ha -1 year -1 ), from July 2007 to September 2008, in temperate grassland in Inner Mongolia, China. Results showed that N fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
38
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 55 publications
8
38
0
3
Order By: Relevance
“…Keeping LAI constant at < 1 (Fig. 7) revealed a still highly significant effect of T a on soil CO 2 fluxes, supporting the notion that management impacts on soil flux magnitudes of CO 2 are rather small compared to environmental drivers (Peng et al, 2011).…”
Section: Co 2 Fluxessupporting
confidence: 64%
“…Keeping LAI constant at < 1 (Fig. 7) revealed a still highly significant effect of T a on soil CO 2 fluxes, supporting the notion that management impacts on soil flux magnitudes of CO 2 are rather small compared to environmental drivers (Peng et al, 2011).…”
Section: Co 2 Fluxessupporting
confidence: 64%
“…The lack of N effect on SR in 2014 may be attributed to the counteractive responses of soil microbial respiration and root respiration to N addition. In the first year, N addition ameliorated the nutrient limitation for microbes; thus, soil microbial activity and biomass increased in the short term (Treseder, 2008) and subsequently stimulated microbial respiration (Peng et al, 2011). On the other hand, N addition could reduce belowground biomass allocation (Haynes and Gower, 1995), leading to a decrease in root respiration.…”
Section: Diverse Responses Of C Flux Components To the N Addition Gramentioning
confidence: 99%
“…It was reported that specific root-derived respiration is higher during early vegetative growth and decline thereafter during reproductive and senescence stages (Fu et al 2002, Sey et al 2010, Jans et al 2010. Further, soil CO 2 emissions have found to be regulated by soil temperature and moisture (Peng et al 2011, Allaire et al 2012, Dhadli et al 2015. Soil moisture coupled with soil temperature and other soil-atmospheric interactions had been found to greatly affect soil CO 2 emissions, and an increase for shorter period after N application was also recorded (Dhadli et al 2015, Mbonimpa et al 2015.…”
mentioning
confidence: 98%
“…Further, cropping systems can influence CO 2 emission by affecting the quality and quantity of C returned to the soil as root biomass or as straw incorporation or mulching (Mapanda et al 2011, Gong et al 2012, Ding et al 2014). Additionally, due to variations in management practices in different cropping systems, soil temperature and water content which directly control CO 2 emission are also influenced (Peng et al 2011, Allaire et al 2012, Zhang et al 2013, Dhadli et al 2015.…”
mentioning
confidence: 99%